2003
DOI: 10.1021/la0350507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microcontact-Printed and Solution-Adsorbed Cytochrome c Films on Indium Tin Oxide Electrodes

Abstract: Three different methods for preparing cytochrome c (cyt c) films on planar indium tin oxide (ITO) electrodes have been characterized and compared using electrochemical and surface spectroscopy methods. Protein films formed by adsorption of dissolved cyt c and by microcontact printing with both hydrophobic and hydrophilic poly(dimethylsiloxane) (PDMS) stamps are compared in terms of the total and electrochemical surface coverage, standard reduction potential, and rate of direct electron transfer with the ITO su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…The electroactive surface coverage is only 9.5 pmol/cm 2 , slightly less than a half monolayer, 18 which shows that less than half of the protein molecules adsorbed on the electrode surface can be directly oxidized or reduced. This could be due to the heterogeneous surface of ITO, 29 which has some insulating regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electroactive surface coverage is only 9.5 pmol/cm 2 , slightly less than a half monolayer, 18 which shows that less than half of the protein molecules adsorbed on the electrode surface can be directly oxidized or reduced. This could be due to the heterogeneous surface of ITO, 29 which has some insulating regions.…”
Section: Resultsmentioning
confidence: 99%
“…18,28 Ten micromolar solutions of ferricytochrome c in 10 mM phosphate buffer (pH 7) were used to prepare all protein films. Deionized (DI) water (18 MΩ) was obtained from a Barnstead Nanopure apparatus and was used throughout.…”
Section: Methodsmentioning
confidence: 99%
“…Above a certain scan rate, the conformational change can be overcome. More recently, Runge and Saavedra showed that cyt C forms a sufficiently stable adsorbed state such that it can be microcontact printed on ITO surfaces, while retaining high electron transfer rates [84]. …”
Section: Modification Using Phosphonic Acids and Other Chemisorbing Fmentioning
confidence: 99%
“…The direct electrochemistry of heme proteins such as cytochrome c and Mb in solution has been successfully observed at bare ITO electrodes [14][15][16][17], which also implies that ITO is an excellent substrate for heme protein immobilization. However, previous work concerning the immobilization of electroactive proteins on ITO has focused on cytochrome c [18][19][20][21]. Although, there is one report mentioning the Mb film on an ITO surface, it was stated that Mb needed to be thoroughly purified and freed from any surface-active impurities in order to observe the electrochemical response [22].…”
Section: Introductionmentioning
confidence: 99%